Effectiveness of Cognitive-Behavioral Therapy on Executive Function and Experiential Avoidance in Veterans with Post-Traumatic Stress Disorder - M. Shafiei; M. Sadeghi; S. Ramezani (Afarand Scholarly Publishing Institute, 2017)
Aims: Impairment in executive functions can result in impaired self-regulatory behavior and social skills deficiency, and experiential avoidance is a strong predictor of psychological signs and symptoms. This study was aimed to evaluate the effectiveness of cognitive-behavioral therapy on executive function and experiential avoidance among veterans with post-traumatic stress disorder (PTSD). Materials & Methods: This study was conducted in a quasi-experimental, pretest-posttest design with control group in 2017. The studied population was included all male veterans with post-traumatic stress disorder referred to Quds hospital in Sanandaj. 40 veterans were selected using available sampling method and were divided randomly in two experimental and control groups. The Wisconsin card sorting test (WCST) and acceptance and action questionnaire (AAQ) were used to collect information. The data were analyzed using SPSS 20 software by multivariate analysis of covariance (MANCOVA). Findings: After controlling the pre-test scores, the results showed that the mean scores of experimental group in number of categories and preservative error as the sub-components of executive function, and experiential avoidance were significantly lower than the control group (p<0.01). Conclusion: Cognitive-behavioral therapy is efficient to increase executive function and to reduce experiential avoidance among veterans with PTSD.